(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the effectiveness of teaching folk crafts and national values in secondary schools using the SMART method, as well as its significance in the spiritual and moral education of the younger generation and its role in preserving and promoting national values. The article also highlights the ways to integrate elements of folk crafts into educational curricula and addresses relevant issues. It is shown that the use of modern SMART methods has increased the level of knowledge acquisition by 30–40%.